Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1513
|View full text |Cite
|
Sign up to set email alerts
|

Driving and Speaking: Revelations by the Head-Mounted Detection Response Task

Abstract: Summary:The cognitive workload of speech-related activity needs to be examined in an economic and simple way. This is especially important as invehicle technology is becoming more cognitive with, for example, the use of speech-interaction and industry will need a way to keep pace with new technologies. One proposed way to measure cognitive workload is the detection response task (DRT) method. In this study, the DRT was used to assess different speech-related cognitive tasks. Three conversation tasks and the n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similar results can be found in Schwalm (2009). Furthermore, similar results were found in the DRT performance of the experiment (Conti et al, 2013).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Similar results can be found in Schwalm (2009). Furthermore, similar results were found in the DRT performance of the experiment (Conti et al, 2013).…”
supporting
confidence: 86%
“…Participants responded by pressing a button on their left index finger. The results for the DRT can be found in Conti, Dlugosch, Schwarz & Bengler (2013).…”
Section: Detection Response Taskmentioning
confidence: 99%
“…The n-back task is known to increase cognitive load in individuals, requiring them to use their working memory to maintain and update information in their minds. The task has been used in several studies to measure cognitive workload in various real-world scenarios, including driving, aviation, and healthcare [18]. The n-back task is an objective measure of cognitive load and can be used in conjunction with other physiological measures, such as EEG, to provide a comprehensive assessment of cognitive workload.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studies conducted at the AgeLab, the task has been used extensively internationally as a method of inducing graded levels of cognitive workload with studies such as [1,2,4,5,6,7,13,21,23,24,26,30] being conducted utilizing the English version of the task or translations into French, German, Chinese, Japanese, Swedish, Korean, and Polish. Various translations of materials provided by international research teams can be found at http://agelab.mit.edu/study-tools.…”
Section: Introductionmentioning
confidence: 99%